2017
DOI: 10.1177/0046958017731963
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Support Issues Affecting Older Patients: A Cross-sectional Paramedic Perspective

Abstract: This research aimed to gain an understanding of the psychosocial support needs of older patients in the out-of-hospital setting from the perspective of paramedics. Specifically, we investigate if and how paramedics are able to meet the needs of older adults, and the barriers preventing them from achieving this. This study was a cross-sectional study utilizing a sequential design with both quantitative and qualitative methodologies. All participants agreed or strongly agreed that older patients have needs beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…1,4 Paramedics encounter a range of behavioral health crises, from individuals who have self-harmed, substance use, to older adults experiencing social isolation. 6,7 This study aimed to answer the following questions: Do paramedics feel well prepared to respond to behavioral health crises? How do paramedics describe the challenges and facilitators involved in responding to these situations?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 Paramedics encounter a range of behavioral health crises, from individuals who have self-harmed, substance use, to older adults experiencing social isolation. 6,7 This study aimed to answer the following questions: Do paramedics feel well prepared to respond to behavioral health crises? How do paramedics describe the challenges and facilitators involved in responding to these situations?…”
Section: Introductionmentioning
confidence: 99%
“…5 In a mixed methods study, Australian paramedics reported the need for more education on how to adequately respond to older adults experiencing complex mental health crises including depression, social isolation, and food insecurity. 7 Limited research has explored paramedic perceptions, attitudes, and experiences responding to behavioral health emergencies, but the existing research indicates that many emergency healthcare providers consider physical health emergencies more valuable or important than behavioral health emergencies. [8][9][10] Studies indicate that paramedic students do not consider training in mental health issues as relevant to the profession, 1 with an Australian study of paramedic undergraduate students indicating a lower level of regard for those with intellectual disabilities, substance abuse disorders, or acute mental illness compared to students studying in other health professions.…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation is most likely, because other losses due to hospitalization, moving away to nursing homes or the death of significant others besides the partner, may additionally affect the integrity of the social network. Despite deserving special attention, there is an undersupply of oldest old individuals with psychosocial and mental health services [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the advantages of improved access to practical help and advice (e.g., dietary changes, exercise advice, guidance with making a will, a Do-Not-Resuscitate order, assistance with tax-free home adaptations, and social prescribing), and medication review, participants reported deriving great benefit from the psychosocial aspect of the nurses’ visits, their active listening, compassion, and personal validation. Psychosocial support concerns in older adults are often a feature of chronic physical health and social support issues [ 41 46 ]. This was particularly true for those in our sample who felt lonely, isolated and ‘forgotten about, which notably included the hearing impaired [ 47 ].…”
Section: Discussionmentioning
confidence: 99%